Dynamics and coherence resonance of tri-stable energy harvesting system - Haitao, Li; Weiyang, Qin; Chunbo, Lan; Wangzheng, Deng; Zhiyong, Zhou (Smart materials and structures, 2016)
To improve the efficiency of energy harvesting, this paper presents a tri-stable energy harvesting device, which can realize inter-well oscillation at low-frequency base excitation and obtain a high harvesting efficiency by tri-stable coherence resonance. First, the model of a magnetic coupling tri-stable piezoelectric energy harvester is established and the corresponding equations are derived. The formula for the magnetic repulsion force between three magnets is given. Then, the dynamic responses of a system subject to harmonic excitation and Gaussian white noise excitation are explored by a numerical method and validated by experiments. Compared with a bi-stable energy harvester, the threshold for inter-well oscillation to occur can be moved forward to the low frequency, and the tri-stable device can create a dense high output voltage and power at the low intensity of stochastic excitation. Results show that for a definite deterministic or stochastic excitation, the system can be optimally designed such that it increases the frequency bandwidth and achieves a high energy harvesting efficiency at coherence resonance.